Conformity Assessment of Citations in English-Language Medical Journals of Iran with the Citation Criteria in Web of Science, PubMed and Scopus Databases - Shahram Sedghi; Somayeh Ghaffari Heshajin (Tehran University of Medical Sciences, 2017)
Background and Aim: Indexing a countrychr('39')s scientific journals in international citation databases can lead to the promotion of its academic status and its participation in global knowledge production. This study aimed to assess the conformity of Iranian English-language medical journals' citations with the objective criteria of journals in the selected databases. Materials and Methods: This was a descriptive, evaluative research. The study population included 52 Iranian English-language medical journals that are not indexed in Web of Science, PubMed and Scopus databases and 465 articles in these issues, and about 11235 citations to the articles. The data have been collected by a checklist. For data analysis, Excel software was used. Results: Some 88.5 percent of journals had a style for writing references; a style that has been observed by most of them. The rate of self-citation was low. Only 2.9 percent of citations were done in the year this study was performed. Journals with 87.2 percent had received the highest number of citations. The old citation time and the imbalance in the types of cited resources were the most important reasons of the weakness of the studied journals and of their not being indexed in the mentioned databases.  Conclusion: Providing valid styles for writing references and controlling the citations accurately should be put on the agenda of journals. The time of references must be newer, and there should be a relative balance in the types of referenced sources.